Perceptions et stratégies d’adaptation au changement côtier aux Comores (Océan indien) - Carola Klöck; Ibrahim Mohamed (VertigO, 2023)
The Comorian coastline has been eroding for decades, as a result of both climate change and local anthropogenic pressure. We here study coastal erosion in the Comoros through a survey of residents in five coastal villages so as to better understand perceptions of coastal erosions, its drivers and the response measures taken. Our survey shows that the local population is aware of coastal erosion, and attributes this problem to two main factors : sand mining as well as sea level rise. However, the population paradoxically favours one single respone measure : hard costal protection through seawalls. These seawalls are largely mal-adaptive : they do not address the problem of sand mining, have short lifespans, and often increase erosion. Respondents seem unaware of these negative effects of seawalls, even if they are well-documented in the Comoros and beyond. More information and education to fight against the « seawall mindset » seems necessary, as does capacity building and better local governance, in particular in contexts of weak governance as in the Comoros.